Uncertainty evaluation in activity measurements with HPGe using two relative methods - Maria Candida Moreira de Almeida; Jose Ubiratan Delgado; Ronaldo Lins Silva; Roberto Poledna; Regio S Gomes; Alfredo L Ferreira Filho (Brazilian Journal of Radiation Sciences, 2022)
Radionuclide metrology laboratories aim to provide radioactive standards for detector calibrations in nuclear safety areas with low uncertainties.  Such standards are applied in nuclear industries, according to the requirements of monitoring programmes. The standard radionuclides of 133Ba, 152Eu and 166mHo are suitable to the determination of efficiency curves in HPGe detectors due to their multi-gamma emissions, which are intense and well separate in the spectrum. With efficiency curves it is possible to do the measurements without needing to use standards. In this work was made a verifying of the uncertainties obtained for the two relative methods: comparative (sample-standard) and efficiency curve. The total uncertainties obtained by sample-standard method varied from 0.4 to 1.2 % (k=1). The results using efficiency curve method are between 0.9 to 2.2 % (k=1).